2009
DOI: 10.1007/bf03326075
|View full text |Cite
|
Sign up to set email alerts
|

Protection of biodiesel and oil from degradation by natural antioxidants of Egyptian Jatropha

Abstract: AB STRACT:Residue of methanolic extract of Egyptian Jatropha curcas contains bioactive substances such as phenolic compounds, which succeeded to be used as natural antioxidants for the protection of oils and their corresponding biodiesel against oxidative deterioration. In the present work, the residue of Jatropha roots were extracted with methanol and resulting residues, were investigated regarding their content of total phenolic compounds by folin-Cioalteau assay. Further, the antioxidant activities of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Moreover, non-antioxidant compounds may also interference the antioxidant activity [31]. Present work showed the favourable results with previous studies on the leaves of Jatropha [8,[15][16][17][18][19][20] and showed equivalent or higher antioxidant activity. As commented before, not only the species but also the extraction protocols used might affect the antioxidant activities.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, non-antioxidant compounds may also interference the antioxidant activity [31]. Present work showed the favourable results with previous studies on the leaves of Jatropha [8,[15][16][17][18][19][20] and showed equivalent or higher antioxidant activity. As commented before, not only the species but also the extraction protocols used might affect the antioxidant activities.…”
Section: Resultssupporting
confidence: 83%
“…), phenolic content, and others bioactivities of different parts of Jatropha [4][5][6][7]9,10]. On the contrary, few studies have focused on leaves [4,8,[15][16][17], roots [17], fruits [18] and others parts [19][20][21] of Jatropha. However, some studies suggested that leaves exhibited higher phenolic content and antioxidant capacity as against to others parts due to phenolic compounds [15][16][17][18][19][20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jatropha curcas is a nut belonging to the Euphorbiaceae family. It is cultivated in central and south America, Southeast Asia, India and Africa and grow well under adverse climatic conditions 8 .…”
Section: Discussionmentioning
confidence: 99%
“…During this stage, up to 100 new radicals are created from one single radical, meaning that the decomposition occurs at an exponential rate and results in the formation of byproducts [15].…”
Section: Introductionmentioning
confidence: 99%